Analysis of The Implementation of The Merdeka Curriculum in Elementary Schools in The Transformation towards A Deep Learning Approach - Anggita, Nia; Angela, Pipin; Rohmah, Adlina Nur; Restya, Dinda; Barokah, Awalina; Setiawan, Bramianto (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum (Kurikulum Merdeka) in elementary schools and the extent to which its application supports the transformation of learning toward a deep learning approach. The Merdeka Curriculum is designed to create flexible, contextual, and student-centered learning, while deep learning emphasizes the development of deep understanding, critical thinking, and reflection. This research employed a descriptive quantitative approach, using a questionnaire distributed to elementary school teachers via Google Form. Data were analyzed using descriptive statistical techniques in the form of percentages and mean achievement scores. The findings indicate that the implementation of the Merdeka Curriculum is in the high category, with most teachers demonstrating the application of deep learning strategies in their teaching practices. Teachers with longer teaching experience tend to achieve higher scores in both aspects. These results suggest a positive relationship between teaching experience and teachers' readiness to transform learning. Therefore, continuous training and pedagogical mentoring should be enhanced, particularly for teachers with shorter work experience, to ensure the equitable and effective implementation of both the Merdeka Curriculum and deep learning.